Salivary Alkaline Phosphatase Level in People with Healthy Periodontium and Generalised Chronic Periodontitis - Koirala, Pramod Kumar; Pradhan, Shaili; Gorkhali, Ranjita Shrestha (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Introduction: Periodontal disease is a multifactorial chronic inflammatory disease affecting the soft and hard supporting structures of teeth leading to alveolar bone loss and exfoliation of involved teeth when left untreated. Traditional periodontal diagnostic methods are not always able to assess present disease states. Saliva as possible biological sample helps measure current disease state, monitor treatment, and indicate prognosis. Oral fluids contain mediators of disease that include microbial host response and bone-specific resorptive markers. Objective: To investigate and compare salivary alkaline phosphatase level in people with healthy periodontium and generalised chronic periodontitis. Methods: This cross-sectional analytical study was conducted in the department of dental surgery, Bir hospital from January to December 2017. Ethical clearance was obtained from institutional review board. Unstimulated saliva sample for the evaluation of alkaline phosphatase was collected from 35 generalised chronic periodontitis (GCP) patients and 35 volunteers with healthy periodontium after informed consent was obtained and periodontal parameters were recorded. Data collected was analysed using SPSS software v.16. Results: Three and half fold increased level of salivary alkaline phosphatase level in GCP patients than healthy volunteers was found which is highly significant. Correlation of salivary alkaline phosphatase level with clinical features of the chronic periodontal disease was observed. Conclusion: An expected benefit of an oral fluid-based periodontal diagnostics would be identification of highly susceptible individuals prior to aggressive disease. Timely detection and diagnosis of disease offer earlier, less invasive, and more cost-effective treatment.